2014
DOI: 10.15740/has/ijae/7.2/422-426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation levels on vegetative growth and yield characteristics in white onion (Allium cepa L.) in Konkan region

Abstract: to assess the effect of irrigation levels on vegetative growth and yield characteristics in white onion on micro-irrigation system. In the present investigation white onion variety Alibag local was tested under three irrigation levels namely I 1 (no deficit), I 2 (20% deficit) and I 3 (40 % deficit) on mini-sprinkler (M 1) and micro-sprinkler (M 2) irrigation methods, while the conventional check basin method was taken as control. The maximum average yield was attained in irrigation level I 1 as 39.82 t/ha, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This shows response of crop to moisture stress and as applied water increased the average weight of onion bulbs increased and it is high at no moisture stress level. The result is in conformity with those obtained by Zayton (2007) and Mane et al, 2014) ANOVA for percentage of dry matter content of onion bulbs showed that there was significant (P < 0.05) influence because of different levels of moisture stress. As indicates in Table 6, the bulb dry matter percentage obtained at T1, T2, T3 and T4 were not significantly different from each other.…”
Section: Effects Of Deficit Irrigation On Growth Parameterssupporting
confidence: 92%
“…This shows response of crop to moisture stress and as applied water increased the average weight of onion bulbs increased and it is high at no moisture stress level. The result is in conformity with those obtained by Zayton (2007) and Mane et al, 2014) ANOVA for percentage of dry matter content of onion bulbs showed that there was significant (P < 0.05) influence because of different levels of moisture stress. As indicates in Table 6, the bulb dry matter percentage obtained at T1, T2, T3 and T4 were not significantly different from each other.…”
Section: Effects Of Deficit Irrigation On Growth Parameterssupporting
confidence: 92%